Assessing the Distinctive Contributions of Simulation & Gaming to the Literature, 1970-2019: A Bibliometric Review. (December 2020) - Nguyen, Uyen-Phuong; Hallinger, Philip
Background. Founded in 1970, Simulation & Gaming has emerged as the leading journal in this field of educational research. Given the centrality the journal's influence, scholars have periodically reflected on the Journal's contributions towards enhancing and refining both research and practice in educational simulation and gaming. Aims. This systematic review aimed toquantitatively document the distinctive contributions of S&G to research and practice on simulations and games over the past 50 years. The review sought to identify the geographic distribution of publications, influential authors and documents published in the Journal, the intellectual structure of the literature, and topics of recent interest. Method. The authors used the Scopus search engine to identify 1, 427 research articles and reviews published in Simulation & Gaming from 1970 through the end of 2019. Bibliometric analyses included descriptive statistics, citation and co-citation and keyword co-occurrence analysis. Results. The review found that while the Journal has increased itsgeographical breadth impressively, the majority of Simulation & Gaming publications continue to be authored by scholars located in Anglo-American-European societies. The review also found that the Journal has become a prime venue for disseminatinginter-disciplinary research on simulation and games. Nonetheless, business simulation/gaming surfaced as the dominant focus in the Journal's content. Analysis of theintellectual structure of the knowledge base confirmed that the field is theoretically anchored in theories ofsocial cognitive and experiential learning . Temporal keyword analysis identified active learning, game design, technology-enhanced simulations and games, and sustainability as topical clusters of recent interest to authors in Simulation & Gaming.